A Dynamic Programming Model for Strategic Materials - Shupp, Franklin R. (The Review of Economics and Statistics, 1964)
IT becomes immediately apparent in analyzing any national economy that some resources are scarce only in the economic sense, but also in the more popular interpretation of that word. Because of international trade these shortages frequently impose no great hardship on the not nation; for example, the absence of tea and coffee plantations in the United States does prevent Americans from consuming prodigious quantities of these beverages. However, in the event of an hostility these resource scarcities can create a serious problem, especially if they happen to include some of the so-called strategic materials. It is with these materials, which are both vital to the country's defense and in short domestic supply, that this paper is concerned. Some of the more publicized scarce resources which have been regarded as critical by the United States include: tin, uranium, manganese, rubber, quinine, diamonds, and possibly plants manufacturing heavy machinery and precision instruments.' The very heterogeneity of this group augurs strongly against finding a single solution or even a unique mode of attack to the problem of how best to assure an adequate supply of these resources under all political conditions. Nevertheless, while the details of any possible solution may vary enormously with the individual material, almost without exception the available policy measures can be fitted into one of the following categories: 1. Importation under all conditions 2. Subsidized domestic production and research 3. Stockpiling 4. Conservation 5. Substitution